The History of the Black Watch (Royal Highland Regiment) of Canada Volume 2: 1939-1945. - Jarymowycz, Roman Johann (McGill-Queen's University Press, 2023)
Roman Jarymowycz recounts the story of the Black Watch (Royal Highland Regiment) of Canada in three volumes, tracing its history from the roots to present day. Through diaries, letters, classified documents, and the regimental archive, he weaves the strands of a complex story into an epic narrative.